KESADARAN HUKUM MASYARAKAT DALAM MELAKSANAKAN PERKAWINAN KE DUA SETELAH PERCERAIAN BERDASARKAN PUTUSAN PENGADILAN DI KABUPATEN SIAK KECAMATAN KOTO GASIB DESA PANGKALAN PISANG - Azet Purnama; Firdaus Firdaus; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
A polyandri marriage has taken place in Pangkalan Pisang Village, Koto Gasib District, Siak Regency. There are 2 (two) polyandri marriages. From the two examples of polyandry marriages that the author described above, actually a legal marriage if between husband and wife are divorced, and the wife may remarry with another man. However, for the case of polyandri marriages that occurred in Pangkalan Pisang Village, Koto Gasib Subdistrict, Siak Regency, it was not carried out according to the proper procedure, namely through divorce first. Proof of divorce can only be proven by a divorce certificate based on Article 8 of the Compilation of Islamic Law which states that the decision of a marriage other than a divorce can only be proven by a divorce certificate in the form of a Religious Court decision in the form of a divorce decision, divorce pledge, khuluk or taklik talak decision. In fact, the greatest difficulty in polyandry, which causes this marriage to fail in practice, is the unknown father of the child born, so that in this model of marriage the relationship between father and son is uncertain.The author defines the main issues as follows about Why Weak Legal Awareness in Implementing a Second Marriage after a Court Decision and so that the community has legal awareness to have legal decisions that remain in divorce prior to the second marriage.This writing when viewed from the type of research it is classified as a sociological legal research and can also be said as field research that examines the applicable legal provisions as well as what happens in reality in the community or in other words a research conducted on the actual reality or actual circumstances that are occur in the community with a view to knowing and finding the facts and data needed to be collected then leads to the identification of problems that ultimately lead to problem solving. Meanwhile, if seen from its nature, this writing is analytical descriptive, which means that the research is intended to provide a detailed, clear and systematic description of the main research problems.From the results of the study, the weak legal awareness of the community in carrying out the second marriage after the court ruling was due to lack of public education and knowledge, coupled with the customary habits of the community as well as the presence of inadequate economic factors, especially for polyandri couples that occurred in Pangkalan Pisang Village, Kecamatan Koto Gasib of Siak Regency while the efforts to make people aware of the law to have legal decisions that remain in divorce prior to the 2nd marriage are done by understanding the existence of positive marriage law and Islamic law and providing legal sanctions against the cancellation of polyandri marriages thus this method reduces the practice of polyandri marriages in Pangkalan Pisang Village, Koto Gasib District, Siak RegencyKeywords: Community-Legal Awareness-Second Marriage After Divorce-Judgment-Pangkalan P Desa Village